Epidemiology and antimicrobial resistance trends of Acinetobacter species in the United Arab Emirates: a retrospective analysis of 12 years of national AMR surveillance data - Thomsen, Jens; Abdulrazzaq, Najiba M.; AlRand, Hussain; , The UAE AMR Surveillance Consortium; Senok, Abiola; Alatoom, Adnan; Agnes-Sonnevend-Pal,; Al Hammadi, Ahmed Abdulkareem; Ahmed, Ahmed Elhag; Yousef, Ahmed F.; Enshasy, Alaa MM; Madhi, Amal Mubarak; et al. (Frontiers in Public Health, 2024)
Introduction Acinetobacter spp., in particular A. baumannii, are opportunistic pathogens linked to nosocomial pneumonia (particularly ventilator-associated pneumonia), central-line catheter-associated blood stream infections, meningitis, urinary tract infections, surgical-site infections, and other types of wound infections. A. baumannii is able to acquire or upregulate various resistance determinants, making it frequently multidrug-resistant, and contributing to increased mortality and morbidity. Data on the epidemiology, levels, and trends of antimicrobial resistance of Acinetobacter spp. in clinical settings is scarce in the Gulf Cooperation Council (GCC) and Middle East and North Africa (MENA) regions. Methods A retrospective 12-year analysis of 17,564 non-duplicate diagnostic Acinetobacter spp. isolates from the United Arab Emirates (UAE) was conducted. Data was generated at 317 surveillance sites by routine patient care during 2010–2021, collected by trained personnel and reported by participating surveillance sites to the UAE National AMR Surveillance program. Data analysis was conducted with WHONET.1 Results Species belonging to the A. calcoaceticus-baumannii complex were mostly reported (86.7%). They were most commonly isolated from urine (32.9%), sputum (29.0%), and soft tissue (25.1%). Resistance trends to antibiotics from different classes during the surveillance period showed a decreasing trend. Specifically, there was a significant decrease in resistance to imipenem, meropenem, and amikacin. Resistance was lowest among Acinetobacter species to both colistin and tigecycline. The percentages of multidrug-resistant (MDR) and possibly extensively drug-resistant (XDR) isolates was reduced by almost half between the beginning of the study in 2010 and its culmination in 2021. Carbapenem-resistant Acinetobacter spp. (CRAB) was associated with a higher mortality (RR: 5.7), a higher admission to ICU (RR 3.3), and an increased length of stay (LOS; 13 excess inpatient days per CRAB case), as compared to Carbapenem-susceptible Acinetobacter spp. Conclusion Carbapenem-resistant Acinetobacter spp. are associated with poorer clinical outcomes, and higher associated costs, as compared to carbapenem-susceptible Acinetobacter spp. A decreasing trend of MDR Acinetobacter spp., as well as resistance to all antibiotic classes under surveillance was observed during 2010 to 2021. Further studies are needed to explore the reasons and underlying factors leading to this remarkable decrease of resistance over time.